The main protease (Mpro) from SARS-CoV-2 triggers plasma clotting in vitro by activating coagulation factors VII and FXII - Anna Pagotto; Federico Uliana; Elena Cavedon; Giulia Nordio; Andrea Pierangelini; Laura Acquasaliente; Maria Ludovica Macchia; Massimo Bellanda; Barbara Gatto; Giustina De Silvestro; Piero Marson; Dario Gregori; et al. (Communications Biology)
Abstract Although the connection between COVID-19 and coagulopathy has been clear since the beginning of SARS-CoV-2 pandemic, the underlying molecular mechanisms remain elusive. Available data support that the hyper-coagulant state is sustained by systemic inflammation. Here we show that the SARS-CoV-2 main protease (Mpro) can play a direct role in the activation of coagulation. Adding Mpro to human plasma increased clotting probability by 3-fold. Enzymatic assays and degradomics analysis indicate that Mpro cleaves and activates coagulation factors VII and XII. This activity is compatible with an extended secondary specificity of Mpro for R↓X that diverge from its well-established preference for LQ↓X. This finding is supported by HDX-MS characterization of the Mpro complex with an Arg-containing inhibitor, as well as the proteolytic cleavage of the peptide FTRLR↓SLEN by Mpro. Overall, integrating biochemical, proteomics and structural biology experiments, we unveil a novel mechanism linking SARS-CoV-2 infection to thrombotic complications in COVID-19.